Oxygen Consumption Rate dan Growth of Koi Fish (Cyprinus rubrofuscus) Cultured in Recirculation System with Different Filter Media - Puluhulawa, Riska (Jurnal Sains dan Teknologi Perikanan, 2025)
This study aimed to analyze the effect of different filtration media in a recirculating aquaculture system (RAS) on the oxygen consumption rate and growth performance of koi fish (Cyprinus rubrofuscus). The RAS was selected to maintain optimal water quality under intensive aquaculture conditions. The experiment was conducted over 30 days using a completely randomized design with four treatments: no filter (control), synthetic fiber, zeolite, and activated carbon, each with three replications. Observed parameters included oxygen consumption rate, specific growth rate (SGR), absolute growth rate in weight and length, and survival rate (SR). The results showed that the use of activated carbon provided the best performance in stabilizing oxygen consumption rate (final value of 0.34 mgO₂/g/jam) and produced the highest SGR (0.485%/day). Treatments with activated carbon and synthetic fiber also achieved the highest survival rates (98.33%). The use of filtration media in RAS significantly improved water quality, supported fish metabolism, and promoted optimal growth and survival of koi fish.